La Cour Pénale Internationale à la croisée des chemins. (2010)
Since the adoption of the Statute of Rome in July 1998, the ICC has been confronted by a number of problems. One such problem is the disagreement which persists among the members of the Assembly of Member States as to whether the crime of Aggression is one over which the Court has competence pursuant to Article 5 of the Statute. Another diffi culty is the opposition of the United States of America which, since the Bush Administration, has deployed a juridical arsenal with the aim of impeding any type of collaboration with the ICC; the tools in the arsenal include the American Service Members’ Protection Act and bilateral immunity agreements which prevent the transfer of American citizens to the Court by State members of the Rome Statute.The entry into force of the of the Statute on 1 July 2002 allowed the Court Prosecutor to initiate the fi rst investigations and processes for war crimes and crimes against humanity committed in the confl icts which have devastated certain African States (D.R.C., The Central African Republic and Uganda). The arrest warrant against the Sudanese President Omar Al Bashir for atrocities committed in Darfur demonstrates the limitations of action on the Court which cannot carry out its mandate without the cooperation of the States. Above all, the Court must confront the criticism of “double standards” and that it is an instrument of “justice for the poor”, while the “powerful” escape. The answers to these problems can be contributed to, in part, through the revision process foreseen by the Statute nine years after its entry into force.